Dopamine D2/3 receptor availability in cocaine use disorder individuals with obesity as measured by [11C]PHNO PET. (1st March 2021) - Matuskey, David; Angarita, Gustavo A.; Worhunsky, Patrick; Koohsari, Sheida; Gravel, Paul; Pittman, Brian; Gaiser, Edward C.; Gallezot, Jean-Dominque; Nabulsi, Nabeel; Huang, Yiyun; Carson, Richard E.; Potenza, Marc N.; et al.
Highlights: This is the first study to examine in vivo dopamine binding in obesity in cocaine use disorder (CUD). Non-obese and obese CUD groups were overall not significantly different using the D3 receptor preferring agonist radioligand [ 11 C]PHNO. Inverse associations between body mass index and D2/3 R availability was observed in the substantia nigra/ventral tegmental area. This differs from previous work in non-CUD individuals and suggests possible desensitization of natural rewards in D3 R-rich midbrain regions. Abstract: Background: Positron emission tomography (PET) work with the dopamine D3 receptor (D3 R) preferring ligand [ 11 C]PHNO in obese individuals has demonstrated higher binding and positive correlations with body mass index (BMI) in otherwise healthy individuals. These findings implicated brain reward areas including the substantia nigra/ventral tegmental area (SN/VTA) and pallidum. In cocaine use disorder (CUD), similar SN/VTA binding profiles have been found compared to healthy control subjects. This study investigates whether BMI-[ 11 C]PHNO relationships are similar in individuals with CUD. Methods: Non-obese CUD subjects (N = 12) were compared to age-matched obese CUD subjects (N = 14). All subjects underwent [ 11 C]PHNO acquisition using a High Resolution Research Tomograph PET scanner. Parametric images were computed using the simplified reference tissue model with cerebellum as the reference region. [ 11 C]PHNO measures of receptor availability were calculated and expressed as non-displaceable binding potential ( BP ND ). Results: In between-group analyses, D2/3R availability in non-obese and obese CUD groups was not significantly different overall. BMI was inversely correlated with BP ND in the SN/VTA (r = -0.45, p = 0.02 uncorrected) in all subjects. Conclusion: These data suggest that obesity in CUD was not associated with significant differences in D2/3 R availability. This in contrast to previous findings in non-CUD individuals that found increased availability of D3 Rs in the SN/VTA associated with obesity. These findings could potentially reflect dysregulation of D3 R in CUD, impacting how affected individuals respond to natural stimuli such as food.